A Fully Transparent and Flexible Ultraviolet–Visible Photodetector Based on Controlled Electrospun ZnO‐CdO Heterojunction Nanofiber Arrays. (27th August 2015) - Zheng, Zhi; Gan, Lin; Li, Huiqiao; Ma, Ying; Bando, Yoshio; Golberg, Dmitri; Zhai, Tianyou
Abstract : It is essential for novel photodetectors to show good photoresponses, high stability, and have facile fabrication methods. Herein, an optimized electrospinning method to fabricate a photodetector based on nanowire arrays that has a wide spectral response range is demonstrated. Arrays of ZnO‐CdO hybrid nanowires are carefully fabricated fusing ZnO and CdO portions into the same nanowires and subsequently assembling those nanowires into a regular structure. Compared to pure ZnO or CdO nanowire arrays, the hybrid arrays show comparable photocurrent/dark current ratios and response speeds, but they possess a much wider spectral response range from ultraviolet to visible light. The optoelectronic and electronic properties of the ZnO‐CdO hybrid nanowire arrays are systematically explored. Based on this, a transparent and flexible photodetector made of ZnO‐CdO hybrid nanowire arrays is fabricated. It shows a high transparency of around 95% in the spectral range of 400–800 nm and maintains its properties even after 200 bending cycles. Importantly, the developed, simple method can be directly applied to many types of substrates and a transfer of the nanowires becomes unnecessary, which guarantees a high quality of the devices. Abstract : A photodetector based on ZnO‐CdO heterojunctions with a large photoresponse range and a fast response speed is fabricated. Its comprehensive photoelectric and carrier transport properties at different wavelengths, light intensities, and pressures are investigated. The detector is highly transparent at 400–800 nm and maintains its properties even after 200 bending cycles. This photodetector has a high potential for use in multicolor optoelectronic devices.